Association of use of different type of manual therapy approach with upper extremity pain in manual therapists of Lahore - Hafiz Muneeb ur Rehman; Zulfiqar, Hunza; Anwer, Hajira; Naina, Nayab (International Health Review, 2026)
This study was conducted to assess the upper limb pain in manual physiotherapists by using different manual therapy techniques.There was no such type of study in Pakistan and also there was less literature found on this study internationally.It was a cross sectional study . Data was collected from the manual physiotherapists of Lahore from different clinical settings. The data collection was done by using Non probability convenient sampling technique. The Sample size was 126, calculated from (“Raosoft” software). The questionnaire used to assess pain was the Standard Nordic musculoskeletal questionnaire. For the statistical analysis, SPSS 20 software was used to find the association of use of a different type of manual therapy approach with upper extremity pain in the manual therapist. The mean age of physiotherapists was 34.6 (SD = 5.996). Out of 126, male physiotherapist 66 and 60 were female. Mostly Physiotherapists who were included in this study had working experience of more than 5 years and practicing more than 3 hours a day had upper limb pain. Physiotherapists using manual therapy techniques Kalterborn technique had more pain in the neck, shoulder, elbow,wrist and hand than physiotherapists using Mulligan and Maitland. There was no association of any technique used by physiotherapists with shoulder, elbow, wrist/hand and neck pain (p>0.05). This study concluded that physiotherapists using Kalternborn technique reported more upper limb pain than therapists using the maitland and mulligan techniques. There was no association of any technique used by hysiotherapists with shoulder, elbow, wrist/hand and neck pain.